Dietary milk fat globule membrane regulates JNK and PI3K/Akt pathway and ameliorates type 2 diabetes in mice induced by a high-fat diet and streptozotocin. (September 2019) - Yuan, Qi-chen; Zhan, Bi-yuan; Du, Min; Chang, Rui; Li, Tian-ge; Mao, Xue-ying
Graphical abstract: Milk fat globule membrane (MFGM) is composed of multiple bioactive molecules including phospholipids, polar lipids, membrane-specific proteins and glycoproteins. This study reports that MFGM alleviates HFD and STZ-induced T2D in C57BL/6J mice by improving glucose and lipid metabolism and sensitizing the PI3K/Akt pathway but suppressing JNK in the liver and skeletal muscle. Highlights: MFGM ameliorated hyperglycemia and dyslipidemia. MFGM ameliorated pathological changes of the liver and pancreas of diabetic mice. MFGM promoted glycogen synthesis by regulating GSK-3β and GS. MFGM improved glucose metabolism by stimulating the PI3K/Akt signaling pathway. Abstract: Milk fat globule membrane (MFGM) was found to possess anti-cancer, anti-obesity and anti-inflammatory activities. The present study was carried out to evaluate the effects and possible underlying mechanisms of MFGM on type 2 diabetes (T2D) in mice. Results showed that 8-week MFGM supplementation had beneficial effects in ameliorating hyperglycemia and dyslipidemia in T2D mice induced with a high-fat diet and streptozotocin. MFGM also protected the liver and pancreas histological structures in T2D mice. Additionally, MFGM enhanced glycogen synthesis, which was associated with inhibition of glycogen synthase kinase 3 beta and activation of glycogen synthase. Furthermore, a mechanistic study illuminated that MFGM likely ameliorated glucose metabolism disorder by promoting the phosphatidylinositol 3-kinase/protein kinase B pathway while suppressing c-Jun N-terminal kinase signaling in liver and skeletal muscle. These findings suggest that MFGM may be useful as a potential functional food ingredient against diabetes.